2021
DOI: 10.1111/ceo.13964
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous seeding in intraocular retinoblastoma: A review

Abstract: The management of retinoblastoma is complex. With increasing treatment modalities and increasing experience with each treatment modality, the globe salvage rates have drastically improved with time. Aqueous seeding in an eye with retinoblastoma is classified as group E based on International Classification of Intraocular Retinoblastoma, and most group E eyes were enucleated a decade earlier. Newer modalities of treatment have improved the globe salvage rates in group E eyes including those with aqueous seeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…As a result, clinicians are observing AC seeds or Schlemm canal invasion in eyes with useful vision, a situation that was previously uncommon. Anterior chamber seeds could be primary in cases of anterior segment invasion, especially in patients with ciliary body infiltration resulting in contaminated aqueous or secondary to spillover of endophytic retinal tumor or vitreous seeds at the vitreous base or ciliary body area . This infiltration is managed in selective cases with intracameral chemotherapy or plaque radiotherapy with acceptable outcomes, with no evidence of systemic metastasis during a short-term follow-up period .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, clinicians are observing AC seeds or Schlemm canal invasion in eyes with useful vision, a situation that was previously uncommon. Anterior chamber seeds could be primary in cases of anterior segment invasion, especially in patients with ciliary body infiltration resulting in contaminated aqueous or secondary to spillover of endophytic retinal tumor or vitreous seeds at the vitreous base or ciliary body area . This infiltration is managed in selective cases with intracameral chemotherapy or plaque radiotherapy with acceptable outcomes, with no evidence of systemic metastasis during a short-term follow-up period .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some authors only inject a small amount of the drug into the AC, with or without paracentesis. 79 When combined with plaque radiotherapy, IcamC led to complete tumor control in a patient who was followed up for 3 years. 80 One study found that IcamC and intravitreal therapy provided good efficacy in treating lesions of the ciliary body and AC.…”
Section: Intracameral Chemotherapymentioning
confidence: 97%
“…Nevertheless, some authors only inject a small amount of the drug into the AC, with or without paracentesis. 79 …”
Section: Intracameral Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Kaliki's article 10 described the current management of aqueous seeding in intraocular retinoblastoma. This review emphasised the need for thorough assessment of seeding using high‐resolution ultrasound biomicroscopy and anterior segment optical coherence tomography, before initiating globe salvage therapies.…”
mentioning
confidence: 99%